2012
DOI: 10.1037/a0025226
|View full text |Cite
|
Sign up to set email alerts
|

Motives for volunteering are associated with mortality risk in older adults.

Abstract: This study adds to the existing literature on the powerful effects of social interactions on health and is the first study to our knowledge to examine the effect of motives on volunteers' subsequent mortality. Volunteers live longer than nonvolunteers, but this is only true if they volunteer for other-oriented reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(209 citation statements)
references
References 38 publications
10
192
1
4
Order By: Relevance
“…Prior research indirectly links the caregiving system with health by showing that prosocial behavior only promotes health and well-being when accompanied by other-focused motivations (Gillath et al, 2005;Konrath et al, 2012) or when extended towards valued others (Poulin et al, 2010). However, a more direct way to study the role of caregiving in health is to examine a key biological mechanism that supports caregiving: the function of the neurohormone oxytocin.…”
Section: Prosocial Behavior Caregiving and Oxytocinmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research indirectly links the caregiving system with health by showing that prosocial behavior only promotes health and well-being when accompanied by other-focused motivations (Gillath et al, 2005;Konrath et al, 2012) or when extended towards valued others (Poulin et al, 2010). However, a more direct way to study the role of caregiving in health is to examine a key biological mechanism that supports caregiving: the function of the neurohormone oxytocin.…”
Section: Prosocial Behavior Caregiving and Oxytocinmentioning
confidence: 99%
“…Recent research supports this view: under acute stress, individuals can become more, not less, prosocial (von Dawans et al, in press). Paradoxically, however, seeking to support others for the express purpose of benefiting the self may be self-defeating, given that prior research has found that such motivations actually undermine the benefits of prosocial behavior (Gillath et al, 2005;Konrath et al, 2012). These prior findings indicate that it may be impractical to advise individuals to cope with stress by engaging in prosocial behavior.…”
Section: Why Do People Need People?mentioning
confidence: 99%
See 1 more Smart Citation
“…Media, advertising, and other popular culture sources reinforce the idea that pampering oneself can lead to increased subjective well-being, reduced stress, and bolstered physical health. Despite these popular notions, however, empirical evidence suggests that prosocial, rather than selffocused, behavior is linked with positive health outcomes (Brown et al, 2003(Brown et al, , 2009Brown and Brown, 2015;Burr et al, 2016;Konrath et al, 2012). Given the strong links between prosocial behavior and broad, long-term physical health outcomes (i.e., cardiovascular disease risk, mortality), surprisingly few studies have experimentally tested whether increasing prosocial behavior leads to improvements in biological processes that may potentially mediate these long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…People with more empathic character traits are also prone to healthier lifestyles, such as less alcohol and tobacco consumption (Adams, 2010;Kalliopuska, 1992), and not surprisingly, they also have better physical health (Dillon & Wink, 2007;Ironson, 2007;Konrath & Fuhrel-Forbis, 2011b). In addition, high empathy in doctors, therapists, and teachers is associated with better outcomes in their patients and students (Aspy & Roebuck, 1972;Beck, Daughtridge, & Sloane, 2002;Chang, Berger, & Chang, 1981;Coffman, 1981;Derksen, Bensing, & Lagro-Janssen, 2013;Kurtz & Grummon, 1972;Truax, et al, 1966;Waxman, 1983;West et al, 2006).…”
mentioning
confidence: 99%